Diseño de un plan estratégico de contingencia para almacenamiento subterráneo de gas natural en el municipio de Zipaquirá, departamento de Cundinamarca como plan decenal 2021-2031. (2021)
Natural gas is one of the most important energy sources worldwide, its storage is one of the most important factors to ensure availability for consumption. Colombia does not currently have a natural gas storage facility for contingencies that may arise. In this sense, this project proposes a strategic contingency plan for the storage of natural gas in salt caverns in the municipality of Zipaquirá, which includes the stages of exploration and investigation, simulation, environmental impact assessment, regulations, construction, operation. / maintenance and dismantling.